Follow-up consultations on growth and development: the meaning for quilombo mothers - Elenilda Farias de Oliveira; Climene Laura de Camargo; Nadirlene Pereira Gomes; Luana Moura Campos; Viviane Silva de Jesus; Maria Carolina Ortiz Whitaker (Universidade Federal do Rio de Janeiro, 2018)
Abstract Objective: To know the meanings of follow-up consultations on growth and development from the perspective of mothers living in quilombos. Method: A qualitative research was carried out with 26 mothers of under one-year-old children who attended the Family Health Unit of Ilha de Maré, Bahia, Brazil. The data of the interviews were systematized using analysis of thematic content based on symbolic interactionism. Results: Four categories were identified that reflect the symbolism of quilombola mothers about child consultations: growth assessment, examination of the general health conditions, guidance on health education, and the identification of health problems/risk factors and intervention. Conclusion: As quilombola mothers see children's consultations in a way similar to that recommended by the Ministry of Health and the scientific evidence shows their relevance to reduce morbidity and mortality rates, this research may guide educational measures aiming at the adherence of more children to the service.